The effect of social assistance on kin relationships: evidence from Roma communities. (2nd January 2020) - Čvorović, Jelena; Vojinović, Željko
ABSTRACT: This paper discusses the effects of social assistance on kinship relationships in Roma, a disadvantaged European minority population, and how variation in kin support affects self-reported health and reproductive success. Data were collected in 2016–7 in several rural Roma settlements in central Serbia. The sample consisted of 143 men and 221 women. Demographic information (e.g., age, gender, educational level, marital and reproductive history, level of socioeconomic status and residence pattern), social assistance history, health status, height, and weight were collected, in addition to kinship relationship dynamics. Receiving social assistance was consistently negatively associated with all measures of kin support, more so for Roma males than females while decreased kin support was found to result in poorer self-rated health and decline in reproductive success.